Wiara podstawowym dynamizmem moralnym osoby - Jóźwiak, Stanisław (Verbum Vitae, 2004)
In a morał apprehension the faith has got a personal character. The development of person is a dynamic process. It includes an intelectual heritage wherein it realizes itself as well as constant internal dispositions what comes from the nature of human person. The theological tradition is a retlection on a biblical understanding o f the faith that apprehends it as a reply to the God’s vocation. That reply is firstly realized within an observation of the Decalogue, then it has got a heteronomical character, and along the development of personality it nextly enters an internal structure of the human subject, where it receives features of the autonomical morality. It is realized within a transition from the morality of Decalogue to the morality of Beatitudes. The mature faith is an attitude of the entire person and her life, and as such it hecomes a fundamental moral dynamism of the human person.